Analisis Kesalahan Linguistik dalam Buku Ajar 'Ayo Belajar Bahasa Arab' Kelas V: Tinjauan Morfologis, Sintaksis dan Semantik - Fezi Safitri; Moch. Mu'izzuddin; Lalu Turjiman Ahmad (Uktub, 2025)
Teaching materials or textbooks play a vital role in the learning process, particularly in language education, as they directly influence the quality and effectiveness of instruction. Linguistic errors in Arabic textbooks often arise from a limited understanding of correct grammatical structures, including both word formation (morphology) and sentence construction (syntax). In Arabic language learning, textbooks serve as a central resource for teaching grammar (Nahwu and Sharaf), vocabulary, reading, writing, listening, and speaking skills. This article aims to examine linguistic errors found in the Ayo Belajar Bahasa Arab textbook for Grade V, published by Erlangga. The study adopts a qualitative approach using library research methods to gather relevant data and theoretical references. The primary source analyzed is the aforementioned textbook. The findings reveal several linguistic issues, including three morphological errors, three syntactic errors, and one semantic error. Morphological errors involve inaccuracies in word endings that affect meaning, syntactic errors relate to improper sentence structure in terms of nahwu, and the semantic error pertains to the misuse or misunderstanding of word meaning within the context of Arabic vocabulary.